2013
DOI: 10.1073/pnas.1212909110
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of charge, hydrophobicity, and sequence of nucleoporins on the translocation of model particles through the nuclear pore complex

Abstract: Fig. 2. Molecular organization of the yeast NPC. Total amino acid (aa) volume fraction (A and D), volume fraction of hydrophobic segments (B and E), and electrostatic potential (C and F) for the native and homogeneous model sequences (Fig. 1). The plots show that homogenizing the amino acid sequence affects the electrostatic potential but not the density of amino acids or the density of hydrophobic amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
202
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(227 citation statements)
references
References 45 publications
23
202
2
Order By: Relevance
“…We found that when expressed as MBP-fusion peptides, substitution of the acidic residues for alanine reduced binding of the N(1-132) sequence to Nup153-FG repeats by ~50% (Fig. 7 A,B), consistent with a reduced electrostatic interaction (42). Interestingly, this was not sufficient to impede the rate of transport.…”
Section: The N-and C-tails Bind Directly To Fg-rich Nucleoporins Of Tsupporting
confidence: 51%
“…We found that when expressed as MBP-fusion peptides, substitution of the acidic residues for alanine reduced binding of the N(1-132) sequence to Nup153-FG repeats by ~50% (Fig. 7 A,B), consistent with a reduced electrostatic interaction (42). Interestingly, this was not sufficient to impede the rate of transport.…”
Section: The N-and C-tails Bind Directly To Fg-rich Nucleoporins Of Tsupporting
confidence: 51%
“…The spacer regions may form nonspecific and transient interactions with NTF2, both providing anchors for rapid recontacting of loose FG motifs, and resulting in a weak multivalency effect. As already suggested (70), electrostatic interactions between the disordered regions and TFs may also play a role similar to the well-characterized effect of electrostatic steering on the kinetics of protein-protein interactions (71). We also observed electrostatic steering due to long-range interaction between the multiple lysine residues in the FG motifs and the acidic patch on NTF2 (residues 91-93), which we shall further investigate in future work.…”
Section: Discussionmentioning
confidence: 71%
“…Cargo lacking NLS may cross the NPC autonomously at a rate dominated by size, but also affected by charge and hydrophobicity (16)(17)(18). At steady state, its concentration will reach a uniform distribution:…”
Section: Passive-only Transportmentioning
confidence: 99%